Digitalizing the Quran and Hadith: Epistemological Reconstruction and Challenges of Religious Authority in the Digital Age - Susanti, Riri; Nurdiansyah, Firgi; Charles, Charles; Gucandra, Yudi (El-Rusyd, 2025)
This study examines how the digital transformation of the Quran and Hadith reshapes Islamic epistemology while maintaining the authenticity and authority of revealed texts in the contemporary technological era. The central issue addressed is the tension between expanded accessibility enabled by digital platforms and the emerging challenges related to textual verification, ethical responsibility, and interpretative accuracy. This research employs a Systematic Literature Review (SLR) by analyzing peer-reviewed national and international publications focusing on the digitalization of sacred texts, artificial intelligence in Islamic studies, and data governance. The analysis follows a thematic and comparative approach through the stages of identification, screening, evaluation, and synthesis, emphasizing philosophical, epistemological, and normative dimensions. The findings reveal that digitalization enhances scholarly engagement, supports innovative da’wah practices, and contributes to the preservation and dissemination of Islamic knowledge. However, it also poses significant risks, particularly the potential for epistemic distortion, algorithmic bias, and weakened mechanisms of sanad and textual authentication. This study argues that the digitalization of the Quran and Hadith must be grounded in ethical frameworks, rigorous scholarly methodology, and sharia-based principles to ensure its legitimacy as a sustainable instrument for Islamic education and religious authority in the digital age.